2015
DOI: 10.1103/physrevd.91.064018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-order operators in nonrelativistic Lifshitz holography

Abstract: In this paper, we study the effects of high-order operators on the non-relativistic Lifshitz holography in the framework of the Hořava-Lifshitz (HL) theory of gravity, which naturally contains high-order operators in order for the theory to be power-counting renormalizble, and provides an ideal place for such studies. In particular, we show that the Lifshitz space-time is still a solution of the full theory of the HL gravity. The effects of the high-oder operators on the space-time itself is simply to shift th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Note that in [273], only the IR limit of the (2+1)dimensional Hořava theory was considered. Later, the effects of high-order operators on the non-relativistic Lifshitz holography were studied [274], and found that the Lifshitz space-time is still a solution of the full theory of the Hořava gravity. The effects of the high-oder operators on the space-time itself is simply to shift the Lifshitz dynamical exponent z.…”
Section: Non-relativistic Gauge/gravity Dualitymentioning
confidence: 99%
“…Note that in [273], only the IR limit of the (2+1)dimensional Hořava theory was considered. Later, the effects of high-order operators on the non-relativistic Lifshitz holography were studied [274], and found that the Lifshitz space-time is still a solution of the full theory of the Hořava gravity. The effects of the high-oder operators on the space-time itself is simply to shift the Lifshitz dynamical exponent z.…”
Section: Non-relativistic Gauge/gravity Dualitymentioning
confidence: 99%
“…The dynamical equations are obtained by varying the action with respect to g ij , and are given by 11) where 12) with L a V ≡ βa i a i . In addition, the matter components (J t , J i , τ ij ) satisfy the conservation laws of energy and momentum,…”
Section: A Field Equations In Ir Limitmentioning
confidence: 99%
“…Some space-times are not complete, and extensions beyond certain horizons are needed. In addition, it was shown recently that the Lifshitz space-time (1.2) is not only a solution of the HL gravity in the IR, but also a solution of the full theory, that is, even high-order operators are all included [11]. The only effects of these high-order operators are to shift z from one value to another, as longer as the spacetime itself is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…The humidity change was chosen from ref. [45]. The device, however, showed a slight degradation of the ON/OFF ratio (from 1.08 to 1.03) as increasing the temperature to 65 °C from 30 °C (Figure S8b, Supporting Information) because the transport of the generated ions in the hydrated MNPs depended on the water content.…”
Section: Figurementioning
confidence: 99%